2020
DOI: 10.1177/0269215520970737
|View full text |Cite
|
Sign up to set email alerts
|

The effects of proprioceptive training on anterior cruciate ligament reconstruction rehabilitation: A systematic review and meta-analysis

Abstract: Objective: To determine the effectiveness of proprioceptive training on knee function and proprioception following anterior cruciate ligament reconstruction. Data sources: PubMed, EMBASE, The Cochrane Library, Ovid, EBMSCO- host, ScienceDirect, CNKI, VIP, WanFang Data and CBM were searched until 2nd October 2020. Review methods: Trials with proprioceptive training for patients with anterior cruciate ligament reconstruction were included. Study screening, data extraction, risk of bias and quality assessments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…They also had lower values of strength and endurance parameters of the knee extensors. These results are similar to those presented in the literature on the assessment of proprioception and knee function [10]. In our opinion, a low self-esteem was associated with worse knee function (lower values of the strength and the endurance parameters in the isokinetic study).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…They also had lower values of strength and endurance parameters of the knee extensors. These results are similar to those presented in the literature on the assessment of proprioception and knee function [10]. In our opinion, a low self-esteem was associated with worse knee function (lower values of the strength and the endurance parameters in the isokinetic study).…”
Section: Discussionsupporting
confidence: 91%
“…Nowadays, proprioceptive training has been demonstrated in the world and has been widely used for patients with an ACL reconstruction [8,9]. Recent trends in ACL rehab are consistently using proprioceptive training with mixed results [10]. Therefore, further work is required to provide evidence.…”
Section: Introductionmentioning
confidence: 99%
“…After searching Chinese and English databases, a total of 2844 related articles were retrieved. Two researchers screened the literatures by reading abstracts and full texts, and a total of 12 articles were included in this study [7–18] . The study selection flow is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The training of proprioception is mainly aimed at balancing function, flexibility and agility. At present the main training methods are: closed power bicycle chain, the balance on the balance board to adjust and control, stability of joint training, visual feedback action program, curve surrounded exercise training on foot, knee, lateral span jumping exercises, different direction and speed of running transformation training such as lateral run, run back, variable speed run, reverse layup, “S” shape run, etc [12] . Although current proprioception training after ACL reconstruction is rich and varied, its specificity and sensitivity still need to be further studied.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, attention to understanding the mechanisms related to neuromuscular control and dynamic stability of the knee in patients with ACL defects has been increasing (12,13). In the rehabilitation process, however, improving proprioceptive and neuromuscular control is one of the little-known issues (14). Today, the use of new technologies such as neurofeedback, biofeedback, and transcranial direct current stimulation (tDCS) as safe and painless methods have been considered to improve brain function, proprioception, and balance (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%